Case Report: Chronic myelomonocytic leukemia initially diagnosed as immune thrombocytopenia - Wu, Jiaxin; Wang, Hongxiang (Frontiers in Hematology, 2026)
ObjectiveTo explore the clinical characteristics, diagnosis and treatment process of a case initially diagnosed with primary immune thrombocytopenia (ITP) and finally diagnosed as chronic myeloid-monocytic leukemia (CMML).MethodsThe clinical manifestations, laboratory tests, bone marrow morphology, molecular genetic test results and treatment history of a CMML patient with thrombocytopenia as the first symptom were retrospectively analyzed.ResultsOne patient was initially diagnosed with immune thrombocytopenia (ITP). After receiving immunosuppressive treatment, the platelets temporarily rebounded, but subsequently the white blood cells increased, the proportion of monocytes increased, and typical CMML-related mutations were found in bone marrow morphology and NGS testing, and he was finally diagnosed as CMML. His condition stabilized after treatment with decitabine chemotherapy.ConclusionCMML can manifest as atypical thrombocytopenia in the early stage, which is delayed by the progression of ITP. Clinical attention should be paid to potential clonal bone marrow diseases in ITP patients who are refractory or have poor response to treatment. Early bone marrow morphological and molecular detection can help to clarify the diagnosis, guide treatment, and improve prognosis.